2014
DOI: 10.1128/aac.02632-13
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Time to Clinical Response and Outcomes among Pneumonia Outcomes Research Team (PORT) Risk Class III and IV Hospitalized Patients with Community-Acquired Pneumonia Who Received Ceftriaxone and Azithromycin

Abstract: Recent Food and Drug Administration (FDA) guidance endorses the use of an early clinical response endpoint as the primary outcome for community-acquired bacterial pneumonia (CABP) trials. While antibiotics will now be approved for CABP, in practice they will primarily be used to treat patients with community-acquired pneumonia (CAP). More importantly, it is unclear how achievement of the new FDA CABP early response endpoint translates into clinically applicable real-world outcomes for patients with CAP. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
13
0
4
Order By: Relevance
“…On average, patients were dis- (14). Similar to the study by Zasowski and colleagues (15), they also observed a predictable lag between the achievement of stability and subsequent hospital discharge (14). There are also some indications that time to clinical stability and being dischargeable may be important determinants of subsequent hospital readmission and death.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…On average, patients were dis- (14). Similar to the study by Zasowski and colleagues (15), they also observed a predictable lag between the achievement of stability and subsequent hospital discharge (14). There are also some indications that time to clinical stability and being dischargeable may be important determinants of subsequent hospital readmission and death.…”
Section: Discussionsupporting
confidence: 67%
“…Given the clear link between the time to clinical stability and hospital discharge (13)(14)(15), these findings may have implications for clinical practice, as ceftaroline may be associated with a shorter time to hospital discharge than that achieved with ceftriaxone among hospitalized patients with CAP, particularly those with only a Gram-positive pathogen(s) at the baseline. The methodology employed here also provides a framework from which to draw comparative effectiveness inferences from phase III CAP efficacy trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Time to clinical response is an important outcome that has previously been associated with several important long-term outcomes. [27][28][29] In addition, we have proposed an efficient, low-resource method by which ASPs can implement rapid diagnostics within their health system. Lack of funding and/or personnel are often cited as barriers to functional and effective ASPs.…”
Section: Discussionmentioning
confidence: 99%